Acute Pancreatitis Unmasking an Ectopic Parathyroid Adenoma in MEN1 Syndrome and Cushing’s Syndrome: A Rare Clinical Convergence - Jafri, Asif Dabeer; Sanjeev, Om Prakash; Nazar, Aftab Hasan; Singh, Ratender Kumar (Acta medica Lituanica, 2026)
Ectopic parathyroid adenoma within the spectrum of Multiple Endocrine Neoplasia Type 1 (MEN1) is an extremely rare clinical entity. We report a 27-year-old woman who presented with acute pancreatitis as the sentinel manifestation of MEN1, an atypical and intriguing clinical scenario. Initially, her serum calcium levels were deceptively normal, only to surge later, unmasking a deeper endocrine pathology. Subsequent biochemical evaluation established primary hyperparathyroidism (PHPT), and a MIBG scan revealed an ectopic parathyroid adenoma as the culprit lesion. Further endocrine profiling disclosed Cushing’s syndrome (CS), confirmed through a low-dose dexamethasone suppression test, while a positive family history of MEN1-related tumors in her sister solidified the syndromic diagnosis. She was treated with aggressive hydration, analgesia, antibiotics, and supportive therapy, followed by successful parathyroidectomy. This case illustrates a remarkable convergence of conditions ectopic parathyroid adenoma, acute pancreatitis, and MEN1 with the additional complexity of initially normocalcemic presentation during the acute phase of pancreatitis. Although the pathophysiological link between hypercalcemia and pancreatitis remains debated, pancreatitis secondary to hypercalcemia from primary hyperparathyroidism is rare, and its presentation as the first clue to MEN1 is exceptionally uncommon. ACTH-secreting pituitary adenomas causing Cushing’s syndrome are also a rare manifestation of MEN1, and the concomitant presence of an empty sella on MRI further underscores the uniqueness of this case. To the best of our knowledge, this represents the first documented instance in which acute pancreatitis with normocalcemia concealed an underlying ectopic parathyroid adenoma in MEN1, accompanied by Cushing’s syndrome and an empty sella, making this a noteworthy clinical and diagnostic rarity.